2015
DOI: 10.1016/j.jnucmat.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Zircaloy-4 with Ti3SiC2 and Ti2AlC in the 1100–1300 °C temperature range

Abstract: h i g h l i g h t sThe diffusion bonding of Ti 3 SiC 2 and Ti 2 AlC to Zircaloy-4 cladding was investigated. Si penetration into the Zr-4 was roughly an order of magnitude less than that of Al. The resultant bonds using Ti 2 AlC were weak and full of cracks. The Ti 3 SiC 2 /Zr-4 bonds were stronger, and withstood the forces of sectioning. a b s t r a c tHerein, we report on the interactions between zirconium, in the form of Zircaloy-4 (Zr-4) and the MAX phases, Ti 3 SiC 2 and Ti 2 AlC in the 1100-1300°C range.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The thickness of the interaction zone was measured under SEM, which was repeated at least 5 times at the different position of joints. Similar method was adopted in other references as well [15,16]. Fig.…”
Section: Diffusion Kineticsmentioning
confidence: 97%
See 1 more Smart Citation
“…The thickness of the interaction zone was measured under SEM, which was repeated at least 5 times at the different position of joints. Similar method was adopted in other references as well [15,16]. Fig.…”
Section: Diffusion Kineticsmentioning
confidence: 97%
“…Finally, the maximum shear strength was obtained at 1000 • C for 10 min, measured to be 120 MPa, which was close to that of Ti 3 SiC 2 . Tallman et al [16] attempted to join the Ti 3 SiC 2 and Ti 2 AlC to Zircaloy-4 for nuclear reactor applications. However, all the diffusion couples fractured during sample mounting, which was mainly attributed to residual stresses during cooling process.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in Zr-to-Si ratio on the oxidized surface at 1000 °C without the preoxidation as confirmed in the XPS analysis, and the local silicon rich area in the cross-sectional image of the coating (Figure 3.13c) also support this explanation. According to the diffusion couple experiments between Ti3SiC2 and Zirc-4 [48], the effective diffusion coefficient of Si in Zirc-4 at 1300 °C was approximately six times larger than that at 1100 °C. Therefore, remarkably rapid silicon loss in the coating, which accelerated by the surface oxidation at 1000 °C in the absence of the protective layer, generated microstructural defects (i.e., clusters of voids) in the coating, which in turn induced the crack formation and intensified material degradation.…”
Section: High Temperature Air Oxidation Of Coatingsmentioning
confidence: 99%
“…The compositional ratio of Si to Zr was slightly reduced (less Si) at 700 °C but it increased again (more Si) at 1000 °C and gets doubled at 1200 °C compared to the as-received ZrSi2. Based on the published high diffusion rate of Si compared to Zr [48,49], it appears that a part of newly formed Si during oxidation diffused inward in the thin oxide layer so that the Si concentration on the surface is diminished during oxidation at 700 °C. However, a net outward flux of Si atoms at the higher temperatures increases the Si concentration on the outer-most surface.…”
Section: Evolution Of Oxide Surface Morphology In Zrsi2mentioning
confidence: 99%
“…For example, it has been shown that Ti 3 SiC 2 has superb corrosion resistance to molten Pb and Pb-Bi alloys [20,21]. The diffusion between Zircaloy-4 and the MAX phases Ti 3 SiC 2 and Ti 2 AlC in the 1100-1300 • C range has also been explored [22]. These results show the A-group element diffusing out of the MAX phase and forming intermetallics with the Zr-4, with the penetration depth of the Si in Ti 3 SiC 2 being roughly an order of magnitude less than that of the Al from the Ti 2 AlC.…”
Section: Introductionmentioning
confidence: 99%